Habitat quality from individual‐ and population‐level perspectives and implications for management. (18th March 2015) - Boves, Than J.; Rodewald, Amanda D.; Wood, Petra B.; Buehler, David A.; Larkin, Jeffrey L.; Wigley, T. Bently; Keyser, Patrick D.
ABSTRACT Many wildlife management prescriptions are either implicitly or explicitly designed to improve habitat quality for a focal species, but habitat quality is often difficult to quantify. Depending upon the approach used to define and identify high‐quality habitat, management decisions may differ widely. Although individual‐level measures of habitat quality based on per capita reproduction (e.g., average nesting success, number of young produced per pair) are most common in the literature, they may not align with population‐level measures that reflect number of young produced within a defined area. Using data on the cerulean warbler (Setophaga cerulea) collected in the Cumberland Mountains (Tennessee, USA; 2008–2010) as an example, we illustrate how lack of concordance between individual‐ and population‐level measures of habitat quality can have real‐world management implications. © 2015 The Wildlife Society.